Parasitic Hymenoptera in The Population of Two Key Pest of Vegetable Soybean Edamame - Hari Purnomo; Intan Nur Rohma; Wildan Muhlison; Irwanto Sucipto (Postgraduate, University of Mataram, 2025)
Whitefly (Bemisia tabaci) and soybean pod borer (Etiella zinckenella) are key pest and notorious on edamame soybean. The investation of the two insects pest can cause up to 80% production of productivity of edamame soybean. The chemical pesticides use is the main tactic to control the pests which have negative impact to infarment and develop insect resistance and resurgence. Identification of natural enemy such as Hymenoptera parasitoids are important effort to promote biological control strategy has alternative infarmentfriendly to control the pests. The results show there is one parasitoid Hymenoptera in soybean pod borer and 5 family of Hymenoptera parasitoid and one family of Diptera parasitoid in whitefly